Identification and quantification of vinpocetine and picamilon in dietary supplements sold in the United States. Issue 3 (1st October 2015) - Avula, Bharathi; Chittiboyina, Amar G.; Sagi, Satyanarayanaraju; Wang, Yan‐Hong; Wang, Mei; Khan, Ikhlas A.; Cohen, Pieter A.
Abstract : Vinpocetine and picamilon are drugs prescribed in many countries to treat a variety of cerebrovascular disorders. In the United States, vinpocetine and picamilon have never been approved by the US Food and Drug Administration, but they are both available for sale directly to consumers as dietary supplements. We designed our study to determine the accuracy of supplement labels with regard to the presence and quantity of vinpocetine and picamilon. A validated ultra‐high performance liquid chromatography‐photodiode‐array method was developed for the quantification of vinpocetine and picamilon. The separation was achieved using a reversed phase (C‐18) column, photodiode array detection, and water/acetonitrile as the mobile phase. Vinpocetine and picamilon were detected at concentrations as low as 10 and 50 ng/mL, respectively. The presence of vinpocetine and picamilon was confirmed using reference standards. Twenty‐three supplements labelled as containing vinpocetine were available for sale at two large supplement retail chains; 17 contained vinpocetine with quantities ranging from 0.3 to 32 mg per recommended daily serving. No vinpocetine was detected in six of the sampled supplements. The supplement label implied that vinpocetine was a constituent of lesser periwinkle in three of the supplements. Of the 31 picamilon supplements available for sale from a variety of retailers: 30 contained picamilon in quantities ranging from 2.7 to 721.5 mg per recommended daily serving. We found that consumers cannot obtain accurate information from supplement labels regarding the presence or quantity of vinpocetine and picamilon. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Vinpocetine and picamilon are two pharmaceutical drugs never approved by the US Food and Drug Administration but sold directly to consumers in dietary supplements. A validated UHPLC‐PDA method was developed for the quantification of vinpocetine and picamilon in dietary supplements. Of the 23 dietary vinpocetine supplements tested, 17 contained vinpocetine and the quantity of vinpocetine ranged from 0.3 to 32 mg per maximum recommended daily dose. Picamilon, also known as nicotinoyl‐γ ‐aminobutyric acid, was found in quantities ranging from 0 mg to 721.5 mg per maximum recommended daily serving.